Assessing essentiality of transketolase in Mycobacterium tuberculosis using an inducible protein degradation system. Issue 1 (1st September 2014) - Kolly, Gaëlle S.; Sala, Claudia; Vocat, Anthony; Cole, Stewart T.
Abstract: Improved genetic tools are required to identify new drug targets in Mycobacterium tuberculosis . To this aim, genetic approaches, targeting either transcription and/or protein degradation, have been developed to appraise gene essentiality and to test the impact of gene silencing on bacterial survival. Here, we successfully combined the Tet-Pip OFF system, which downregulates transcription through the TetR and Pip repressors, with SspB-mediated protein degradation to study depletion of the transketolase encoded by the tkt ( rv1449c ) gene. We show that depletion of Tkt using the RNA silencing and protein degradation (RSPD) system arrested growth of M. tuberculosis in vitro faster than the Tet-Pip OFF system alone. In addition, we extended the new combined approach to an ex vivo model of M. tuberculosis infection in THP-1 cells. Tkt-depleted bacteria displayed reduced virulence as compared to wild type bacilli, thus confirming the essentiality of the enzyme for intracellular growth. Abstract : Essentiality of the transketolase enzyme, Tkt, of M ycobacterium tuberculosis was confirmed by attaching a regulating promoter and a protein degradation tag to the tkt gene. Abstract :